Nanogels of Succinylated Glycol Chitosan-Succinyl Prednisolone Conjugate: Preparation, In Vitro Characteristics and Therapeutic Potential - Haiyan Zhou; Atsuko Ichikawa; Yuri Ikeuchi-Takahashi; Yoshiyuki Hattori; Hiraku Onishi (MDPI AG, 2019)
A novel anionic nanogel system was prepared using succinylated glycol chitosan-succinyl prednisolone conjugate (S-GCh-SP). The nanogel, named NG(S), was evaluated in vitro and in vivo. S-GCh-SP formed a nanogel via the aggregation of hydrophobic prednisolone (PD) moieties and the introduced succinyl groups contributed to the negative surface charge of the nanogel. The resultant NG(S) had a PD content of 13.7% (w/w), was ca. 400 nm in size and had a ζ-potential of −28 mV. NG(S) released PD very slowly at gastric pH and faster but gradually at small intestinal pH. Although NG(S) was easily taken up by the macrophage-like cell line Raw 264.7, it did not decrease cell viability, suggesting that the toxicity of the nanogel was very low. The in vivo evaluation was performed using rats with trinitrobenzene sulfonic acid (TNBS)-induced colitis. NG(S) and PD alone were not very effective at 5 mg PD eq./kg. However, NG(S) at 10 mg PD eq./kg markedly suppressed colonic damage, whereas PD alone did not. Furthermore, thymus atrophy was less with NG(S) than with PD alone. These results demonstrated that NG(S) is very safe, promotes drug effectiveness and has low toxicity. NG(S) has potential as a drug delivery system for the treatment of ulcerative colitis.